2020
DOI: 10.1177/1071100720961315
|View full text |Cite
|
Sign up to set email alerts
|

3D Assessment in Posttraumatic Ankle Osteoarthritis

Abstract: Introduction: Auto-generated 3-dimensional (3D) measurements based on weightbearing cone-beam computed tomography (CT) scan technology may allow for a more accurate hind- and midfoot assessment. The current study evaluated the reliability and clinical relevance of such measurements in patients with posttraumatic end-stage ankle osteoarthritis. Methods: Seventy-two patients treated at our institution for posttraumatic end-stage ankle osteoarthritis, with available weightbearing conventional radiographs and a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
47
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 40 publications
0
47
0
Order By: Relevance
“…In many previous similar papers from CBCT scans in fact the angles were taken still in planar views, i.e. in the most appropriate single CT image 10 , 17 , 19 , 37 , 40 , 42 44 , 54 , 55 and not exactly from 3D models of the foot bones as in the present work. The entire process here present (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In many previous similar papers from CBCT scans in fact the angles were taken still in planar views, i.e. in the most appropriate single CT image 10 , 17 , 19 , 37 , 40 , 42 44 , 54 , 55 and not exactly from 3D models of the foot bones as in the present work. The entire process here present (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Thereafter, the software automatically registered a mathematical model of each bone on the original rendered image. The software also computed the location of anatomical landmarks and longitudinal axes of the bones of interest 37 , but this feature was not used in the present work.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Further, de Cesar et al conducted a similar study of patients with a substantial flatfoot deformity and found that WBCT imaging better demonstrated the severity of deformation in the medial cuneiform-to-floor distance and forefoot arch angle when compared to NWBCT conditions [26]. While other studies do exist that measure foot and ankle alignment using WBCT vs. NWBCT or WBPR [27][28][29][30][31][32], to the authors' knowledge, no studies exist in current literature comparing the sensitivity and specificity of NWBCT and WBCT performance in midfoot OA. Recently, Willey et al used WBCT to demonstrate significant postoperative ankle joint-space narrowing in patients who underwent surgical treatment for a tibial pilon fracture [33].…”
Section: Discussionmentioning
confidence: 99%